Rise and fall of the dust shell of the classical nova V339 Delphini - Evans, Aneurin; Krautter, Joachim (Arxiv, 2016)
We present infrared spectroscopy of the classical nova V339 Delphini, obtained over a $\sim2$ year period. The infrared emission lines were initially symmetrical, with HWHM velocities of 525 km s$^{-1}$. In later ($t\gtrsim77